2020
DOI: 10.1088/1361-6382/ab7964
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of perturbations from a coherent quantum inflationary horizon

Abstract: It is proposed that the inflationary horizon in holographic quantum gravity imprints primordial scalar curvature perturbations with a distinctive pattern whose correlations differ from the standard quantum theory of inflation. Holographic and causal constraints are used to formulate candidate directional symmetries of perturbations in the angular domain. It is suggested that this hypothesis could provide a physical explanation for several well known anomalies measured in CMB anisotropy. New exact symmetries ar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

6
1

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 87 publications
1
22
0
Order By: Relevance
“…We have argued previously [35][36][37][38][39] that causal constraints in holographic space-times lead to constraints on large angular scale correlations in the cosmological system. Here, we investigate the consequences of the specific conjecture that the angular spectrum C and correlation function C(Θ) of primordial curvature perturbations on spherical surfaces around any comoving world line approximate universal functions at large angles, governed by the requirement that correlations of invariant scalar curvature among different world lines arise entirely from causal entanglement within their horizons.…”
Section: Causal Constraints On Large-angle Correlationsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have argued previously [35][36][37][38][39] that causal constraints in holographic space-times lead to constraints on large angular scale correlations in the cosmological system. Here, we investigate the consequences of the specific conjecture that the angular spectrum C and correlation function C(Θ) of primordial curvature perturbations on spherical surfaces around any comoving world line approximate universal functions at large angles, governed by the requirement that correlations of invariant scalar curvature among different world lines arise entirely from causal entanglement within their horizons.…”
Section: Causal Constraints On Large-angle Correlationsmentioning
confidence: 99%
“…The same is true for points on the great circle normal to any polar direction: there is no opportunity for information from a plane tangent at a pole to causally affect correlations of ∆ on its great circles. Since values of ∆ on any great circle are independent of polar values, it follows [25,38,39] that C(π/2) = 0.…”
Section: Antihemispherical Causal Constraints a Vanishing Correlation...mentioning
confidence: 99%
See 1 more Smart Citation
“…Equation (28) is the main result of this paper, the angular pattern of time displacement recorded on the surface of the causal diamond. Since the weighting falls off as ∼ 1/l 3 , the l = 2 mode will be the dominant contribution.…”
Section: Time Displacementmentioning
confidence: 99%
“…The decomposition of the correlations into spherical harmonics Y m l derived in this way has most of its power in low l modes, which motivates the prediction that the transverse correlations extend over macroscopic angular separations, as mentioned above. Moreover, it has been suggested that the angular power spectrum of the temperature fluctuations in the CMB is a manifestation of this fundamental decomposition in spherical harmonics of quantum fluctuations on an inflationary horizon [29].…”
Section: Introductionmentioning
confidence: 99%